ANALISIS PEMAHAMAN MATEMATIS SISWA DALAM MENYELESAIKAN OPERASI BENTUK PANGKAT DAN AKAR KELAS X - Tiara Enika Putri (Jurnal Pendidikan, 2023)
The ability to understand is the ability to understand in depth a concept by empowering logical, critical, creative, and innovative minds and being able to take responsibility for a concept. Type of research: qualitative with a descriptive approach to describe students' ability to understand mathematics in completing exponential and root operations in class X SMA Muhammadiyah 2 Pontianak. The subjects of this study were 13 students who had studied the number material with the previous rank. The data collection technique used in this study is the provision of tests and interviews. From the results of research and discussion obtained the following percentages: 1) Restating a concept 15%. 2) Presenting concepts in various forms of mathematical representation 6%. 3) Using and utilizing and selecting certain procedures or operations 41%. 4) Applying concepts in problem solving 42%. It can be concluded that students' understanding of mathematical concepts is still low in understanding questions related to exponential and root forms, describing the path of solving the problem and applying the concept of exponential forms and roots appropriately. The researcher suggests that the teacher should pay attention to the different abilities of students' understanding of concepts. So that it can provide a more detailed explanation of students who do not understand the material being taught and this research should be used as comparison material for future researchers.